Sensorial triad as a gateway to museums - Martins, Cláudia (2017)
Storytelling is acknowledged as an invaluable element when audiodescribing for the blind and visuallyimpaired be it for the screen or for other venues, such as museums and galleries or historical and archaeological sites. This technique allows cultural events to become accessible to these patrons by means of expressive, imaginative and vivid language entangled in description and narration, thus words become images in people’s minds. There is no denying that it also enables to turn any cultural and aesthetic experience into emotionally significant. Many scholars have highlighted the danger of AD becoming too subjective, thus the American-European divide: on the one hand, the American tendency for objective AD (e.g. Snyder, 2004), whereas, on the other, the European that contends for a freer practice. In line with this inclination, we could mention Anne Hornby, an experienced British audiodescriber, who upholds that AD tells a story, and Neves (2008), a Portuguese researcher and practitioner, who has been carrying out ‘soundpainting’ experiments, an extra layer of meaning that allows feelings to be aroused. The latter pushes the boundaries of an already subjective tendency and underlines the importance of sound and careful choice of words, concerns stressed out in “Art Beyond Sight” (Axel et al., 1996), as well as in “Pictures painted in Words: ADLAB Audio Description Guidelines” (ADLAB, 2014). Notwithstanding, Guigue (2010), Confino-Rehder (2010) and Neves (2014) also mention another dimension of the necessary triad, that is to sounds and text we must add the object which, for lack of visual perception, must become a tactile material, so as to activate the audiences’ sense of touch. We intend to retrieve examples from our doctorate research, which aimed at analysing a sample of audioguides offered in Portuguese museums, in order to ascertain the extent to which these texts would encourage this multisensorial experience.